Adição de enzimas em dietas de frangos de corte a base de milho de diferentes qualidades - Andrade, Tiago Vieira de (2020)
The nutritional quality of stored corn grains is of paramount importance to formulate more efficient diets, given that corn grains with low nutritional value, trigger metabolic disturbances and consequently negative effects on the performance and use of nutrients in birds. Thus, the objective was to evaluate the effect of the addition of exogenous enzymes in diets of broilers based on corn kernels of different qualities. with 696 birds of the Cobb 500 strain. In experiments 1 and 3, with the purpose of evaluating performance at 1, 7, 21, 35 and 42 days of age and intestinal histomorphometry at 21 and 42 days of age, 600 chicks were used 1 day old males. In experiments 2 and 4, metabolism assays were carried out with 96 14-day old male chicks from experiment 1 and 3 to estimate the metabolizable energy values of corn of different qualities with the inclusion of exogenous enzymes and mycotoxin adsorbent in diets for broilers. In all experiments, a completely randomized design (DIC) was used, distributed in a factorial arrangement (2x2), with experiment 1 and 2 being the addition or not of the XAP enzyme blend (Xylanase, Amylase and Protease) and two types of corn (types 1 and 3), and for experiment 3 and 4 with or without the addition of mycotoxin adsorbent and with or without the addition of the enzymatic blend. It was observed that the birds that consumed type 1 corn with enzyme had higher average weight and better feed conversion. It was observed that the birds that consumed diets containing enzyme showed better digestibility for the values of EMAn, EMA and CMMS in the period of 17 to 21 days. It was observed that birds that consumed type 1 corn with enzyme showed better intestinal development for height of the jejunum and ileum up to 21 days of age. There was a reduction in uric acid and AST for birds that consumed type 1 corn with enzyme. There was a reduction (p <0.05) in LDH for birds that consumed type 1 corn. There was a higher (p <0.05) average weight for birds that consumed diets containing enzyme and adsorbent in the period from 1 to 7 days . In conclusion, it can be said that birds that consumed type 1 corn with enzyme showed good performance, carcass yield, use of nutrients and intestinal development.